Customized Laser Vision Correction (Springer International Publishing, 2018)
This book addresses customized laser vision correction and integral management options for the treatment of irregular corneas. This type of treatment reshapes the corneal surface in order to improve both the quality and the quantity of vision by reducing high order aberrations. Beginning with an introduction to the basics of this science, the three types of customized laser vision correction are then discussed by experts in this field. Throughout this practical guide, clinical examples are supported with the most recent scientific material and a step-by-step systematic methodology to fit all levels of ophthalmologists. .